MANAJEMEN PENDIDIKAN AKHLAK SANTRI - Sarmila Sarmila; Nurdin K; Kartini Kartini (Kelola: Journal of Islamic Education Management, 2022)
The main problem in this study was the description of the management and application of moral education of students in the Babussa'adah Bajo Modern Islamic Boarding School. Methodologically this research was a qualitative research by searching, analyzing and making interpretation of data found through document studies, interviews and observations. The data that had been collected were checked for validity through data validity standards in the form of trustworthiness, reliability, reliability and certainty. The data analysis technique used was reducing, displaying and drawing conclusions from the results of the study. The results of the research are: 1. Planning of moral education in the Islamic Boarding School of Babussa'adah Bajo since its inception, placing morals as a top priority in the preaching and education movement, 2. Organizing is done by establishing tasks, responsibilities, and authority as well as work mechanisms so that the objectives can be achieved, 3. Implementation of moral education in Modern Islamic Boarding School Babussa'adah Bajo puts the perfection of morality as the main target in the process of moral education, 4. Supervision of moral education of students is carried out jointly with the big family of Islamic boarding schools, local communities and parents of students, 5. Evaluation of moral education in Modern Islamic Boarding School Babussa'adah Bajo shows a significant increase, especially in its application in daily life both in the boarding school environment and family environment. Babussa'adah Bajo Modern Islamic Boarding School places the perfection of morality as the main target in the process of Islamic education and the target that becomes the reference in moral education is to produce outputs that can be a role model for the community.